Altered purinergic P2X7 and A2B receptors signaling limits macrophage-mediated host defense in schistosomiasis - Maria Luiza Thorstenberg; Monique Daiane Andrade Martins; Nathália Ferreira Oliveira; Matheus Macedo L.V. Monteiro; Gustavo R.C. Santos; Henrique M. Gualberto Pereira; Luiz Eduardo Baggio Savio; Robson Coutinho-Silva; Claudia Lucia Martins Silva (Biomedical Journal)
Background: The occurrence of co-infections during schistosomiasis, a neglected tropical disease, with other parasites have been reported suggesting an impaired host immune defense. Macrophage purinergic P2X7 receptor (P2X7R) plays an important role against intracellular pathogens. Therefore, we investigated the P2X7R-mediated phagocytosis and killing capacity of Leishmania amazonensis by macrophages during schistosomiasis in vitro and in vivo. Methods: Swiss and C57BL/6 (Wild type) and P2X7R−/− were randomized in two groups: control (uninfected) and Schistosoma mansoni-infected. Alternatively, control Swiss and S. mansoni-infected mice were also infected with L. amazonensis. Results: The pre-treatment of control macrophages with the P2X7R antagonist (A74003) or TGF-β reduced the phagocytosis index, mimicking the phenotype of cells from S. mansoni-infected mice and P2X7R−/− mice. Apyrase also reduced the phagocytosis index in the control group corroborating the role of ATP to macrophage activation. Moreover, l-arginine-nitric oxide pathway was compromised during schistosomiasis, which could explain the reduced killing capacity in response to ATP in vitro and in vivo. We found an increased extracellular nucleotide (ATP, ADP and AMP) hydrolysis along with an increased frequency of F4/80+ CD39+ macrophages from the S. mansoni-infected group. Moreover, the content of adenosine in the cell supernatant was higher in the S. mansoni-infected group in relation to controls. Schistosomiasis also increased the expression of macrophage adenosine A2BR. In good accordance, both ADA and the selective A2BR antagonist restored the phagocytosis index of macrophages from S. mansoni-infected group. Conclusions: Altogether, the altered P2X7R and A2BR signaling limits the role of macrophages to host defense against L. amazonensis during schistosomiasis, potentially contributing to the pathophysiology and clinically relevant co-infections.